Think of Pair Share Learning Model on Student Learning Activity in Science Subjects at State Elementary Madrasah - Hasanah, Asri Nur; Baharudin, Baharudin; Hasnanto, Anton Tri (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This research is motivated by the low activity and learning outcomes of students in natural science subjects at state elementary schools. This study aims to test and analyze the effect of the Think Pair Share (TPS) learning model on increasing the engagement and learning outcomes of fifth-grade science subject students at State Elementary Schools. This study uses a quasi-experimental method with a post-test-only nonequivalent control group design. The sample consists of two groups: the Experimental Class (n=27), which applies the TPS model, and the Control Class (n=26), which uses conventional learning at State Elementary School 3 Bandar Lampung. Data was collected through questionnaires, observation of learning activities, and learning outcome tests (post-test). Learning outcome data was analyzed using the independent sample t-test (Welch's t-test) after normality and homogeneity tests. The results of the study show: (1) Student learning engagement in the Experimental Class is in the High category with an average of 78.7%, while the Control Class is in the medium category with an average of 59.9%. (2) The average post-test score of the experimental class (88.52) was much higher than that of the control class (69.04). (3) The results of the hypothesis test indicated that there was a statistically very significant difference between the two groups (p-value = 0.000000019), which indicated that H_0 was rejected. The contribution of this study is to provide empirical evidence that the TPS learning model is a very effective and significant intervention in improving learning activities and cognitive learning outcomes among science students in elementary Islamic education.